Computational molecular evolution - Yang, Ziheng (Oxford series in ecology and evolution., 2006)
Covering the modern statistical and computational methods used in molecular evolutionary analysis, such as maximum likelihood and Bayesian statistics, this book is useful for students and professional researchers in the fields of molecular phylogenetics, population genetics, mathematics, statistics and computer science.